Pengaruh Pendekatan Problem Posing terhadap Kemampuan Berpikir Kreatif Matematis dan Kecemasan Siswa SMP - Murhamah Amri; M. Ikhsan; Saminan Saminan (Jurnal Peluang, 2019)
The result of PISA and TIMSS showed that students' mathematics abilities Indonesia is still low, including the ability to think creatively. The ability to think creatively influenced by psychological factors, one of them is anxiety. The efforts that teachers can do to improve creative thinking and coping with anxiety is applying problem posing approach. The problem posing approach can make students creative in issuing ideas to create questions and resolve them through three forms of cognitive activity, namely: presolution posing, within solution posing and posing post solution, then it ramble positive anxiety of students in learning. This study aims to determine the increase in the mathematics creative thinking ability and changes anxiety in learning by using problem posing approach. The study uses a quantitative approach to the type of experimental design pretest-posttest control group. The collecting data by using mathematics creative thinking ability tests and questionnaires anxiety. The data were analyzed using t-test and Two Way Anova. The results showed that the overall increase in the mathematical creative thinking ability of students taught through problem posing approach better than students taught through conventional learning. The same is also happened for students with medium and low KAM. As for students with high KAM increase creative thinking abilities of students taught through problem posing approach is no better than students taught through conventional learning. The results also show that there is no interaction between the learning and human factors to improving the students' ability to think creatively. In addition, overall there is a decrease both anxiety in students being taught by problem posing as well as conventional, as the decrease of anxiety in intention is the decrease of anxiety with ideal criteria. The decrease anxiety in students taught with problem posing better than conventional students. It also happens to students with high and medium.